2018
DOI: 10.1111/sji.12637
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Group 2 Innate Lymphoid Cells is Associated with Chronic Inflammation and Dysregulated Metabolic Homoeostasis in Type 2 Diabetic Nephropathy

Abstract: The metabolic syndrome (MS) is an independent risk factor for type 2 diabetic nephropathy and accompanied by subclinical inflammation which involves immune-deriving factors. Emerging studies indicate that group 2 innate lymphoid cells (ILC2s) can regulate adipose metabolism, but much less is known about the activity of ILC2s in metabolic imbalance in obesity and diabetes. This study explored the effect of ILC2s-related molecules on the occurrence of MS in type 2 diabetic nephropathy. Thirty patients with type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…In the absence of ILC2, the numbers of AT‐resident eosinophils and M2‐like macrophages are significantly reduced . Recently, Lu et al have shown that increased activity of ILC2s in T2D patients with nephropathy causes chronic inflammation and abnormal metabolic homeostasis . Oldenhove et al revealed that in HFD‐fed mice, elevated levels of TNF‐ɑ and IL‐33 in the AT increase the expression of programmed cell death‐1 (PD‐1) on ILC2s and impair their functions in the presence of PD‐L1 + M1‐like macrophages .…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of ILC2, the numbers of AT‐resident eosinophils and M2‐like macrophages are significantly reduced . Recently, Lu et al have shown that increased activity of ILC2s in T2D patients with nephropathy causes chronic inflammation and abnormal metabolic homeostasis . Oldenhove et al revealed that in HFD‐fed mice, elevated levels of TNF‐ɑ and IL‐33 in the AT increase the expression of programmed cell death‐1 (PD‐1) on ILC2s and impair their functions in the presence of PD‐L1 + M1‐like macrophages .…”
Section: White Adipose Tissue (Wat) In Health and Obesitymentioning
confidence: 99%
“…6 Recently, Lu et al have shown that increased activity of ILC2s in T2D patients with nephropathy causes chronic inflammation and abnormal metabolic homeostasis. 132 Oldenhove et al revealed that in HFD-fed mice, elevated levels of TNF-ɑ and IL-33 in the AT increase the expression of programmed cell death-1 (PD-1) on ILC2s and impair their functions in the presence of PD-L1 + M1-like macrophages. 133 O'Sullivan et al have shown that after HFD in mice, immune cell-derived IL-12 in the AT causes rapid proliferation and activation of IFN-γ-producing ILC1s, which induce macrophage polarization towards M1-like phenotype and promote IR.…”
Section: Ilcsmentioning
confidence: 99%
“…Pre-denaturation was performed at 95˚C for 5 min, denaturation was performed at 95˚C for 30 sec, annealing was performed at 72˚C for 30 sec and extension was performed at 65˚C for 1 min. Fold changes in the expression of each gene relative to β-actin were calculated using the comparative threshold cycle (Ct) method (13). All experiments were performed in triplicate.…”
Section: Reverse Transcription-quantitative (Rt-q)pcr Analysismentioning
confidence: 99%
“…Since two independent studies suggested increased numbers of ILC2s and type 2 cytokines (IL-4, IL-5, IL-13) in the peripheral blood of patients suffering from CKD due to type 2 diabetes (45,46), it can be speculated that ILC2s might be a marker for renal fibrosis in human CKD. However, technical limitations in the flow cytometry gating strategy used to identify ILC2s in these studies preclude valid conclusions from these data and further research is clearly needed to assess a potential role of ILC subsets in human CKD.…”
Section: Ilcs In Chronic Kidney Diseasementioning
confidence: 99%